Pengaruh Pendapatan Ijarah Terhadap Profitabilitas (ROA) Pada PT Bank Syariah Mandiri Tbk Periode 2015-2019 - Suhartono Suhartono; Dyah Octavia; Fahmi Kamal; Lukman Hakim; Taat Kuspriyono; Teni Agustina (Universitas Pamulang, 2021)
One of the functions of the bank is to collect public funds which are used for the benefit of all parties. There are many factors that can increase bank profits in managing public savings. The purpose of this study is to determine the impact of ijarah income on profitability (ROA) in BSM. The data used by researchers is quantitative secondary data from the 2015-2019 period using statistical methods of correlation coefficient test, coefficient of determination test, and simple linear regression test. Where the data is processed using manual calculations with the SPSS v20 formula and application with the results of the correlation coefficient test of 0.906 or 90.6%, which means that the correlation level of ijarah income to profitability (ROA) is very influential with the degree of perfect correlation level. For the results of the determination coefficient test of 0.820 or 82% because the calculation results are close to 1, it means that ijarah income has a positive impact on profitability (ROA). Simple linear regression with a calculated F value of 82.848 with a significance level of 0.000, it can be concluded that there is an effect of Ijarah Income on Profitability (ROA).